Simplifying and accelerating kinetics enabling fast-charge Al batteries. Issue 45 (11th November 2020) - Mao, Minglei; Yu, Ze; Lin, Zejing; Hu, Yong-Sheng; Li, Hong; Huang, Xuejie; Chen, Liquan; Liu, Miao; Suo, Liumin
Abstract : AlCl2 + coordination with carbonyl groups enables a fast-charge Al battery. Abstract : Nowadays, cost-efficient and high-power energy storage technologies are urgently required for extensive integration of intermittent wind and solar renewable energy. Complying with the simplification and acceleration principle, we designed a fast-charge Al organic battery in which ionic diffusion in anode materials and through the solid electrolyte interphase (SEI) process is simplified while the generation of charge-carrier ions at the cathode/anode interface and ion diffusion in cathode materials are accelerated. A prototype based on 2, 3, 5, 6-tetraphthalimido- p -benzoquinone (TPBQ)–Al was successfully demonstrated with 100 mA h pouch cells displaying superior power capability, high energy density and excellent cycling stability. Moreover, extensive characterizations and DFT calculations predict the crystal structure and simulate the precise reaction pathway corresponding to the thermodynamic redox potential of TPBQ and consolidate our proposed AlCl2 + electrochemical surface-coordination and storage mechanism. We believe that our design philosophy by simplifying and accelerating kinetics would provide guidance for tailoring fast and affordable energy storage systems.